Pengembangan Kode Etik sebagai Tenaga Kependidikan di Pondok Pesantren - Muhith Maulana; Astuti Darmiyanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
In line with these provisions, important principles in the employment profession as teachers at Islamic boarding schools must be upheld. In an effort to realize religious principles in life in the Islamic boarding school world, the role and function of enforcing the Code of Ethics as a profession that complies with regulations at Islamic boarding schools, is independent and responsible is important, in addition to Islamic educational institutions and the Al Islamic Boarding School Foundation. -Sincere. Through the educational services provided, the interests of Santriwan/Santriwati, including efforts to provide education in realizing their rights and obligations as teachers, can be realized. In the study of Islamic Religion, it is argued that apart from religious norms, there are also other norms that contribute to maintaining order in the world of Islamic boarding schools, which are called ethical norms. The ethical norms of various professional groups are formulated in the form of a professional code of ethics. Code of ethics are moral principles attached to a profession and arranged systematically. The professional code of ethics is a norm established and accepted by professional groups, which directs or gives instructions to its members how to act and at the same time guarantees the moral quality of the profession in the eyes of the public, students and other teaching staff. The general principles formulated in a profession will vary from one another. The code of ethics functions: As a means of social control, preventing interference from other parties, preventing misunderstandings and conflicts, as a control whether members of professional groups have fulfilled their obligations. The objectives are: Upholding the dignity of the profession, protecting and maintaining the welfare of the teachers, increasing the dedication of the teachers, improving the quality of the profession and organization, improving services, strengthening the organization, avoiding unfair competition, establishing close relationships with teachers, and setting standards. Teachers at Islamic boarding schools must comply with important norms in upholding the teachings of Islam, namely: humanity, fairness in teaching, propriety, honesty and carrying out the code of ethics as appropriate. But in practice sometimes it doesn't go well and even creates problems. In its application sometimes it experiences obstacles or obstacles. The discussion in this study is: Theoretical Framework: Grand theory: Ethical theory, Middle range theory: Balance theory, Applied theory: Justice theory; Ethics, morals, norms, laws and relationships; Professional code of ethics for teaching staff at Islamic boarding schools: Code of ethics and guidelines for caretakers of Islamic boarding schools, code of conduct for ustadz/ustadzah, professional code of ethics for other teaching staff at Islamic boarding schools, code of ethics for treasurer of Islamic boarding schools; Implementation of a good teaching profession and Obstacles or obstacles in implementing the professional code of ethics for Education staff at Islamic Boarding Schools. The method used is survey research. If a problem occurs regarding the implementation of the code of ethics, it should be resolved by taking into account the principles contained in the code of ethics.